Підвищення якості контролю знань студентів з іноземної мови за допомогою дистанційних засобів, Placement test для оптимізації процесу - Чубукіна, Ольга Володимирівна; Танько, Євгенія Владиславівна; Вракіна, Вікторія Вікторівна (Видавництво "Молодий вчений", 2020)
Досліджено шляхи підвищення якості контролю знань студентів з іноземної мови за допомогою дистанційних засобів, зокрема Placement Test як початкової ланки навчального процесу. Проаналізовано місце, функції і значення Placement Test у навчанні іноземної мови і тестовому контролі його результатів. Охарактеризовано переваги і недоліки тестового контролю, вимоги до тестів та їхню структуру. Висловлено міркування про перспективність адаптації у вітчизняних ЗВО систем «вхідного» тестування Inside Out, Oxford Online Placement Test, English First, C-Test, зокрема у дистанційних формах. На матеріалі узагальнення результатів застосування Placement Test аргументовано необхідність його доповнення усною співбесідою з метою виявлення іномовної комунікативної компетенції. Вказано на доцільність узгодження структури тесту з професійною спрямованістю, освітніми програмами і рівнем мовної підготовки студентів того чи іншого ЗВО.

The ways of quality improvement for knowledge control in a foreign language with the help of distance tools, especially the Placement Test as the initial step in the educational process are investigated. The place, functions and meaning of Placement Test in the overall process of foreign language’s learning and control of its result are analyzed. The advantages of testing, test requirements and structure are described. The structure, pros and cons of Inside Out, Oxford Online Placement Test, English First, C-Test implemented worldwide as a part of the foreign language learning are considered. The prospects of their adaptation in the national Higher Educational Institutions (HEIs), in distance learning in particular, are demonstrated. The efficiency of using computer adaptive tests for entrance testing is emphasized since they allow to quickly, qualitatively and reliably determine the basic level of foreign language proficiency. It is highlighted that the advantage of adaptive tests lies in increasing the measurement accuracy and reliability and significant test time reduction because the fewer tasks are required to determine the level of students' fundamental knowledge. The emphasis is laid on the advisability of publishing the Placement Test on HEI website though combining its results with those of an oral interview in the classroom to assess foreign language communicative competence. It is noted that the Placement Test allows to determine the real level of students' fundamental knowledge, plan further educational activities, define their priorities, ensure an individual approach to the process participants. The Placement Test has proved to be efficient for improving the quality of organization of further educational process. Based on the results of using the Placement Test in the Department of Foreign Languages of M.Ye. Zhukovskyi National Aerospace University "Kharkiv Aviation Institute" and the Department of Foreign Languages of National Technical University “Kharkiv Polytechnic Institute” it has been proved that it is necessary to adapt the Test structure to the professional direction, educational programs of specific HEI and level of students' language proficiency.
Knowledge Control Quality Improvement of Students in a Foreign Language with the Help of Distance Tools and Placement Test for the Process Optimization
Keywords: іноземна мова; дистанційне навчання; тестовий контроль; Placement Test; рівні мовної підготовки; рівневе навчання; foreign language; distance learning; assessment tests; levels of language proficiency; proficiency